2020
DOI: 10.1002/ptr.6790
|View full text |Cite
|
Sign up to set email alerts
|

Clinical efficacy and safety of Tanreqing injection combined with antibiotics versus antibiotics alone in the treatment of pulmonary infection patients after chemotherapy with lung cancer: A systematic review and meta‐analysis

Abstract: This study aimed to evaluate the efficacy and safety of Tanreqing injection (TRQi) in the treatment of pulmonary infection after chemotherapy in patients with lung cancer. Cochrane Library, PubMed, Web of Science, EMbase, CNKI, VMIS, Wan‐Fang, and CBM databases were comprehensively searched from established to March 2020. randomized controlled trials (RCTs) of TRQi were selected. The evaluation manual of Cochrane RCT was used to evaluate the methodological quality of all included studies, Stata 13.0 and Review… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…This is the first phase B clinical study to evaluate the efficacy and safety of pembrolizumab in advanced NSCLC. It was found that the effect was better in patients with elevated PD-L1 expression [34]. A total of 14 RCTS of pembrolizumab treatment for NSCLC were included in this study.…”
Section: Discussionmentioning
confidence: 99%
“…This is the first phase B clinical study to evaluate the efficacy and safety of pembrolizumab in advanced NSCLC. It was found that the effect was better in patients with elevated PD-L1 expression [34]. A total of 14 RCTS of pembrolizumab treatment for NSCLC were included in this study.…”
Section: Discussionmentioning
confidence: 99%
“… [11] Its efficacy and safety have been confirmed in influenza, lung infection, and other diseases. [ 11 , 12 ] Tanreqing injection has been used in the treatment of mycoplasma pneumonia in children for many years, and it could improve the curative effect, shortening the course of disease, and reducing the side effects of Azithromycin. [13] However, there is no strict randomized controlled trial (RCT) to study the efficacy of Tanreqing injection combined with azithromycin in the treatment of MP in children.…”
Section: Introductionmentioning
confidence: 99%